The Effect Of Work Discipline And Work Skills On The Performance Of Operational Employees With Job Satisfaction As An Intervening Variable In Sub Holding Pelindo Multi Terminal Branch Belawan - Muhammad Rifqi Maulana; Sri Rahayu; Kholihul Kholik (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to find out and analyze the influence of work discipline and work skills on the performance of operational employees with job satisfaction as an intervening variable in the sub holding of Pelindo Multi Terminal Branch Belawan. The population in this study is 186 people. The number of samples taken was 127 respondents (using the Slovin formula). This study uses quantitative primary data collected through questionnaires and processed with PLS smart software applications. This research will be carried out in 2025. The analysis technique used using the analysis path model. The results showed that Work Discipline (X1) had a positive effect on job satisfaction (Z), with a path coefficient value (Original Sample column) of 0.454, and a P-Values value = 0.00, Work Discipline (X1) had a positive effect on performance (Y), with a path coefficient value (Original Sample column) of 0.392, and a P-Values value = 0.003, Work Skills (X2) have a positive effect on job satisfaction (Z), with a path coefficient value (Original Sample column) of 0.438, and a P-Values value = 0.00, Work Skills (X2) have a positive effect on Performance (Y), with a path coefficient value (Original Sample column) of 0.456, and significant with a P-Values value = 0.00, Job satisfaction (Z) has a positive effect on Performance (Y), with a path coefficient value (Original Sample column) of 0.507, and a P-Values value = 0.003, Work performance (Y) significantly mediates the relationship between work disciplines (X1) through job satisfaction with a path coefficient value (original Sample column) of 0.23, and significant with a p-Values value = 0.036, Work performance (Y) significantly mediates the relationship between work skills (X2) through satisfaction work with a path coefficient value (original column of the sample) of 0.222, and significant with a value of p-Values = 0.038.